Niche differentiation between Malus sylvestris and its hybrid with Malus domestica indicated by plant community, soil and light. (9th October 2021) - Ahl, Lisa; Aas, Gregor; Walentowski, Helge; Höltken, Aki Michael; Feulner, Martin
Abstract: Question: Malus sylvestris is considered an endangered tree species in Central Europe. Hybridization with Malus domestica poses a serious threat to the genetic integrity of the wild species. Here we investigate whether M . sylvestris and the hybrid M. domestica × s ylvestris occur in the same habitat or have different ecological niches and whether M . sylvestris is threatened by displacement by the hybrid. Location: Northern Bavaria. Methods: Taxon delimitation was accomplished using six genetic microsatellite markers and 613 Germany‐wide references of M . sylvestris and 75 cultivars. To determine differences in the ecological niches between M . sylvestris and hybrids, light availability for the trees was estimated via gap fractions in hemispherical photographs. Soil particle size fractions and pH values were determined for each horizon. Vegetation relevé data were collected, and mean Ellenberg indicator values calculated. For habitat differences, means in combination with frequency patterns of the parameters were compared, and logistic models and detrended correspondence analysis (DCA) of community data were calculated. Results: Genetic markers identified 22 M . sylvestris and 11 hybrid specimens, meaning that in the study area the wild taxon is much more frequent than the hybrid. Ecological site differences between M . sylvestris and its hybrid with M . domestica were best explained by light availability, pH and mean Ellenberg moisture value. In contrast to the ecological demands of the hybrid, Malus sylvestris tolerated wet soil and flooding and even somewhat shadier conditions in the later successional stages. DCA revealed that differences in the composition of the plant communities in which the taxa were found were primarily driven by soil moisture. Conclusions: Our data suggested different ecological niches, which are appropriate to reduce the risk of replacement of M . sylvestris by the hybrid M . domestica × sylvestris . Hence, these findings provide important implications for a more targeted planning of in‐situ conservation strategies of M . sylvestris genomes with low levels of admixture and help to protect plant communities suitable for the threatened wild apple. Abstract : Hybridization with Malus domestica poses a serious threat to the genetic integrity of Malus sylvestris . Based on a genetic delimitation of Malus sylvestris against M . domestica × sylvestris, we investigated its phytosociological optima, soil requirements, and light demand. Distinct distribution patterns suggested niche partitioning of the two taxa, reducing the risk of replacement of M . sylvestris by the hybrid.